Subacute aflatoxicosis due to moldy bread consumption in a dog - Eroksuz, Y.; Kaya, E.; Issi, M.; Baydar, E.; Cevik, A.; Eroksuz, H.; Timurkan, O. (Ecole Nationale Veterinaire Toulouse, 2015)
A 2-year-old male Anatolian shepherd dog was delivered to Firat University veterinary emergency service in a comatose state with a history of anorexia and was in poor general condition with icterus, epistaxis and melena. Marked elevation of alanine aminotransferase (474 IU/L), alkaline phosphatase (463 IU/L), hyperbilirubinemia (9.15 mg/dl) and blood urea nitrogen (192 mg/dl) were highly suggestive of hepato-renal failure. Despite intravascular supportive fluid administration, the dog died two hours after arrival. This patient was the fourth dog to die from the same farm within an eight day period. The necropsy revealed severe diffuse icterus, severe and diffuse intestinal intraluminal hemorrhage, unclotted hemorrhagic fluid in the thoracic and abdominal cavities, enhanced lobular pattern in the liver, mesenteric arterial thrombosis, diffuse splenic, pancreatic and gastrointestinal edema and plant material in the stomach. The main histological findings in the liver included centrilobular hemorrhagic necrosis, degenerative changes, moderate cytomegaly, cholestasis and regenerative nodule formation. Aflatoxin exposure was confirmed by determining the levels of aflatoxins (B1, B2, G1, G2) or their metabolite (M1) in the bread included in the dog's diet (AFB1: 326 mu g/kg, AFB2: 142 mu g/kg, AFG1: 1542 mu g/kg, AFG2:1151 mu g/kg, AFM1:72 mu g/kg), in the liver (AFB1: 0.35 mu g/kg, AFG1: 0.32 mu g/kg, AFG2: 0.75 mu g/kg, AFM1: 1.70 mu g/kg) and in the urine (AFG2: 2.55 mu g/kg, AFM1: 8.60 mu g/kg) by HPLC. Aspergillus flavus and Aspergillus parasiticus were isolated from bread samples. Tests for leptospirosis, adenovirus infection and mushroom intoxication (alpha, beta and gamma amanitins) were all negative. Unique morphological changes including mesenteric arterial thrombosis and renal tubular megalocytosis have not been reported before in association with canine aflatoxicosis.
Keywords: Aflatoxicosis; Aspergillus; contaminated bread; dog; hepatotoxicity